2012
DOI: 10.1001/jama.2012.156
|View full text |Cite|
|
Sign up to set email alerts
|

Moderate to Vigorous Physical Activity and Sedentary Time and Cardiometabolic Risk Factors in Children and Adolescents

Abstract: Higher MVPA time by children and adolescents was associated with better cardiometabolic risk factors regardless of the amount of sedentary time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
860
14
37

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 996 publications
(966 citation statements)
references
References 49 publications
55
860
14
37
Order By: Relevance
“…Six (32)(33)(34)(35)(36)(37) cross-sectional studies were identified including between 398 and 20 871 participants. All studies assessed physical activity by accelerometry and outcome measures were BMI, BMI z-score, waist circumference and body composition (e.g.…”
Section: Does Physical Activity Predict Gain In Adiposity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Six (32)(33)(34)(35)(36)(37) cross-sectional studies were identified including between 398 and 20 871 participants. All studies assessed physical activity by accelerometry and outcome measures were BMI, BMI z-score, waist circumference and body composition (e.g.…”
Section: Does Physical Activity Predict Gain In Adiposity?mentioning
confidence: 99%
“…However, recently this assumption has been challenged and some have suggested that physical activity at baseline is unrelated to weight gain at follow-up, but that the converse was true, since greater adiposity levels at baseline was significantly related to lower levels of physical activity or an increased risk of becoming sedentary at follow-up, suggesting reverse causality (35,51,52) . Kwon et al (51) examined the associations between objectively measured time in MVPA by accelerometry, with gain in fat mass in 326 US children, in which objectively measured physical activity and fat mass was available at three time points.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Cada vez son más los investigadores que tratan de paliar los riesgos psicosociales asociados al ámbito laboral apoyándose en los trabajos científicos existentes que relacionan la práctica de actividad física con la salud física, mental y social (Ekelund et al, 2012) y la calidad de vida (Martínez & Calvo, 2014). Entre las diferentes opciones de práctica físico-deportiva, el método Pilates ha irrumpido con fuerza en nuestra sociedad (Boix, León, & Serrano, 2014) y es practicado por millones de personas en todo el mundo (Chang, 2000;Muirhead, 2004).…”
Section: Introductionunclassified
“…For example, excessive sedentary behavior has been associated with premature all-cause and cardiovascular disease mortality, obesity and an unfavorable cardiometabolic risk factor profile in adults 2 . Regarding this behavior in youth, although evidence is more limited, excessive sedentary behavior appears to have a harmful effect on health 3,4 . Consequently, educational and public health organizations have focused efforts on promoting a decrease in sedentary behavior from an early age 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Since several sedentary activities are part of young people's daily routine (e.g. : classes at school, studying), sedentary activities during leisure time are the target of preventive strategies 4 . Among youth, the most common leisure-time sedentary behavior is watching television (TV).…”
Section: Introductionmentioning
confidence: 99%